BUILDING TRUST IN UNIVERSITY-LEVEL ENGLISH LANGUAGE EDUCATION IN INDONESIA: A MIXED METHODS STUDY - Suryanto Suryanto (Indonesian Journal of Learning and Instruction, 2024)
Trust in others is shown when an individual is prepared to prioritize their well-being without considering potential risks, driven by their unwavering belief in the moral integrity of others. The research investigates the degree of trust between students and teachers in English language instruction. It examines the underlying factors contributing to this trust and investigate the strategies teachers and students use to establish trust. The researcher used a mixed methods approach by integrating questionnaires and interviews to gather data for this study. The surveys were provided to 265 students using convenient sampling, while the interviews were purposefully conducted with ten lecturers and 18 students. The researcher used descriptive statistics to analyze the data obtained from the questionnaire. Given that 63.7 % of students express trust in their instructors, the findings suggest that the degree of trust between students and professors is typically positive in the context of university-level English instruction. The interview data were examined using open, axial, and selective coding techniques. The study's findings indicate a reciprocal trust between students and teachers, with students demonstrating a solid foundation for this trust. In response, lecturers possess effective strategies for cultivating students' trust